Herd-Level Risk Factors for Swine Influenza (H1N1) Seropositivity in West Java and Banten Provinces of Indonesia (2016–2017) - Nurhayati,; Wibawa, Hendra; Mahawan, Trian; Zenal, Farida Camallia; Schoonman, Luuk; Pfeiffer, Caitlin Nicole; Stevenson, Mark; Punyapornwithaya, Veerasak (Frontiers in Veterinary Science, 2020)
Swine could play a role as a ‘mixing vessel’ for avian and human influenza viruses and should, therefore, be thought of playing an intermediate role in the emergence of pandemic influenza strains. The aim of this study was to identify risk factors for SIV seropositivity at the farm level in West Java and Banten provinces, Indonesia. A total of 649 blood samples were collected from 175 pig farms, and at the time of sampling a questionnaire about routine herd management was administered to participant herd managers. SIV serological status for each of the sampled pigs was tested using the IDEXX ELISA test (Maine, US). The apparent herd-level prevalence of SIV seropositivity was expressed as a true herd-level prevalence using the Rogan and Gladen method, modified to account for low and high prevalence herds using a Markov chain Monte Carlo Bayesian approach. The association between herd-level characteristics and SIV seropositivity status was assessed using binary logistic regression. The true prevalence of SIV seropositivity was 26 %(95% CI= 20-33). The presence of animals apart from pigs on farm (odds ratio [OR]= 2.51, 95%CI=1.0-6.0), keeping breeding sows for less than 2 years (OR= 5.9, 95% Cl= 1.8-20), being less than one kilometre from a poultry farm (OR= 2.4, 95% Cl= 1.0-5.7) and purchasing pigs only through pig collectors (OR=11, 95% CI= 4.3-29) increased the risk of a herd being seropositive to SIV. Our results show that biosecurity to limit the introduction of SIV should be enhanced on farms located in areas of high pig and poultry farm density. While the role pig collectors play in transmission of SIV warrants further investigation, swine producers in West Java and Banten should be made aware of the enhanced risk of SIV associated with purchasing of replacements from collectors.